Pesticide thiram exposure alters the gut microbial diversity of chickens - Wu, Zhiwen; Su, Rongsheng (Frontiers in Microbiology, 2022)
Thiram is a vital dithiocarbamate pesticide commonly found in polluted field crops, feed and rivers. Environmental thiram exposure has been demonstrated to cause angiogenesis and osteogenesis disorders in chickens, but information regarding thiram influences on gut microbiota, apoptosis and autophagy in chickens has been insufficient. Here, we explored the effect of thiram exposure on gut microbiota, apoptosis and autophagy of chickens. Results demonstrated that thiram exposure impaired the morphology and structure of intestinal and liver tissues. Moreover, the gut microbiota in chickens exposed to thiram exhibited a obvious decline in alpha diversity, accompanied by significant shifts in taxonomic compositions. Bacterial taxonomic analysis showed that thiram exposure cause a significant reduction in the levels of 8 genera as well as a obvious increase in the levels of 2 phyla and 10 genera. Among decreased bacterial genera, 7 genera even cannot be observed in the thiram-inducted chickens. Overall, this study demonstrated that thiram exposure not only dramatically altered the gut microbial diversity and composition but also induced liver apoptosis and autophagy in chickens. Importantly, this study also conveys a key message that the dysbiosis of gut microbiota may be one of the vital pathways for thiram to exert its toxic effects.